Management of HER2-Positive Early Breast Cancer in Italy: A Maze Presenting Opportunities and Challenges - Stucci, Luigia Stefania; Pisino, Marco; D’Addario, Claudia; Grassi, Teresa; Toss, Angela (Frontiers in Oncology, 2022)
The management of human epidermal growth factor receptor 2 (HER2)-positive early-stage breast cancer (BC) has changed in recent years thanks to the introduction of anti-HER2 agents in clinical practice as standard of care in the neoadjuvant setting. In this scenario, we probed the issue of which HER2-positive BC pts are eligible for neoadjuvant or for adjuvant treatment, since these therapeutic strategies seem to be mutually exclusive in clinical practice according to Italian drug surveillance system. We reviewed both alternatives to establish which is more suitable, considering the anti-HER2 drugs available in Italy. Randomized clinical trials demonstrated a similar clinical benefit for chemotherapy administered as neoadjuvant therapy or adjuvant therapy. A meta-analysis, including 11,955 patients treated with neoadjuvant therapy, demonstrated an improvement in event-free survival (EFS) and overall survival (OS). Moreover, the recent APHINITY trial, analyzed at 6-years follow-up, demonstrated the superiority of the combination Pertuzumab-Trastuzumab versus Trastuzumab-placebo in previously untreated pts. A greater benefit was found in patients with positive lymph nodes treated in the adjuvant setting. Our analysis underlines need for a therapeutic decision-making algorithm, that is still unavailable, to support clinicians in identifying patients suitable to neoadjuvant or adjuvant therapy. Further prospective clinical trials should be performed in collaboration with other Italian Breast Cancer Centres to establish the best strategy to be adopted in early HER2+ BC.